A comparative analysis of hub connections of European and Asian airports against Middle Eastern hubs in intercontinental markets - Piltz, Christopher; Voltes-Dorta, Augusto; Suau-Sanchez, Pere (Elsevier, 2017)
In a context of changing trends in global air passenger demand and strong airport and airline competition, the largest US carriers have challenged the quality of the flight connections provided by Middle Eastern hubs in direct competition with their own connections provided via European or Asian airports. Using schedules and bookings data between 2012 and 2016, we assess whether European and Asian hubs have lost market share to Middle East airports in the markets from the Eastern US to South Asia and South East Asia. Thereafter, we provide a comparative analysis of the quality of flight connections for selected European, Asian, and Middle Eastern airports, based on indicators like total frequencies, travel times, and connecting times (determined with a connections-building algorithm). The results provide insights on the threat posed by Middle East airports and airlines that have managerial and policy implications.
Keywords: Airport connectivity; Hub competition; Airline network development